2016
DOI: 10.1177/0194599816630726
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Changes Caused by Endoscopic Endonasal Transsphenoidal Surgery and Their Effects on Nasal Functions

Abstract: Endoscopic endonasal transsphenoidal approach surgery altered the patients' nasal anatomy, but the changes in nasal cavity dimensions did not affect nasal functions and symptoms. These results will help surgeons to appropriately expose the surgical field during endoscopic endonasal transsphenoidal approach surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 28 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…Access to the pituitary gland must compromise between creating sufficient space for tumor extraction and preserving nasal anatomical structures. Disruption of the normal nasal anatomy can lead to the postoperative deterioration of the nasal functions, especially the sense of smell [10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Access to the pituitary gland must compromise between creating sufficient space for tumor extraction and preserving nasal anatomical structures. Disruption of the normal nasal anatomy can lead to the postoperative deterioration of the nasal functions, especially the sense of smell [10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the sample‐size calculation, Kim et al 17,18 have reported that ILST‐induced intranasal volume changes do not correlate with objective olfactory changes after binostril EETS, suggesting that the overall impact of ILST on olfaction is minimal. In an earlier study of endoscopic sinus surgery (ESS), the incidence of objective olfactory decline after PRST was 12% in patients with chronic rhinosinusitis 19 .…”
Section: Methodsmentioning
confidence: 99%
“…-Changes in the volume (mm 3 ) of both nasal cavities on acoustic rhinometry between postoperative 3 months and current status. -Changes in cross-sectional area of nasal cavity [at the ostiomeatal unit (OMU) level; mm 2 ] on coronal view CT images [11] between postoperative 3 months and current status.…”
Section: Secondary Outcomesmentioning
confidence: 99%